2022
DOI: 10.11591/ijere.v11i2.22131
|View full text |Cite
|
Sign up to set email alerts
|

The perception on mobile-based interactive learning media use in archiving course completion

Abstract: <span lang="EN-US">This research analyzed the discriminant of different categories of successfully passing and remedial students based on the perception on mobile-based interactive archiving media. The research method employed quantitative approach with questionnaire instrument. The questionnaire was distributed to students attending Archiving class using interactive archiving media having been developed by the author previously. Data analysis involved prerequisite test analysis including validity and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…So, it can be said that this media, as a complement to learning, is able to increase learning outcomes by 16%. The results of this study prove that learning media is a tool that can help the teaching and learning process so that the meaning of the message conveyed becomes clearer and the goals of education or learning can be achieved effectively and efficiently [23]- [25]. Effective learning certainly requires good planning, also supported by good learning facilities and media.…”
Section: Discussionmentioning
confidence: 69%
“…So, it can be said that this media, as a complement to learning, is able to increase learning outcomes by 16%. The results of this study prove that learning media is a tool that can help the teaching and learning process so that the meaning of the message conveyed becomes clearer and the goals of education or learning can be achieved effectively and efficiently [23]- [25]. Effective learning certainly requires good planning, also supported by good learning facilities and media.…”
Section: Discussionmentioning
confidence: 69%
“…It has been demonstrated that including interactive media into the learning process improves students' capacities. In accordance with this, Ninghardjanti, Huda & Dirgatama (2022) discovered that students' perceptions of interactive media-based mobile learning, particularly the media originality focus indicator, became a factor of efforts to enhance student learning outcomes. This is evident from past research.…”
Section: Discussionmentioning
confidence: 83%
“…The use of mobile learning has been proven to significantly improve student learning outcomes. Research shows that mobile learning can enhance students' learning results (Fathurohman et al, 2023), while its implementation can also expand students' thinking skills (Ninghardjanti, 2022;Suyatmo et al, 2023). Through mobile learning, students can more easily access diverse information and learning materials, thus helping them develop critical and analytical thinking skills.…”
Section: Discussionmentioning
confidence: 99%